The formation of Argentina's Masters program in Social Science - Garcia de Fanelli, Ana M. (Education Policy Analysis Archives, 2001)
The article describes the main features of Argentine Social Science Masters programs and evaluates the extent to which they are developing innovative strategies in the present conservative institutional context. The research was based on nineteen case studies of Masters in public and private universities. Quantitative data were also gathered from those Masters that were accredited by the National Commission of Evaluation and Accreditation (CONEAU). All these data are analyzed in terms of the program's objectives, inputs, processing and output indicators. The paper concludes with an analysis of the restrictions that limit the suitable development of academic and professional postgraduate courses in Argentina.